MEDICINAL ASSESSMENT OF KENAF (Hibiscus cannabinus L.): ANTIBACTERIAL, PHYTOCHEMICAL, AND NUTRITIONAL PROFILING - Sulaiman, Mustapha; Abubakar, Amina Lawan; Muhammad, Ma’aruf Abdulmumin; Shafi’i, Abubakar Muhd; Idris, Inuwa Musa; Iya, Naseer Inuwa Durumin (FUDMA Journal of Sciences, 2024)
While pharmaceutical drugs often come with detrimental side effects such as liver damage and addiction, the Hibiscus cannabinus L. (kenaf) plant has proven to be a promising traditional medicinal alternative. However, there are extremely few studies to investigate the variability of medicinal and nutritional parameters in Kenaf tissues. The phytochemicals, proximate composition, mineral content, amino acid content, and antibacterial activity of kenaf tissues have been studied and compared using advanced techniques. UPLC analysis reveals that leaves contain the highest concentration of caffeic acid (76.4 mg/100 g), which is also present in stem bark (51.3 mg/100 g). GC-MS analysis shows linoleic acid is predominant in seeds (46.23%) and stem bark (40.7%), while E-Phytol is mostly in leaves (33.5%) and hexadecanoic acid in flowers. Phenolic analysis indicates water as the most effective extraction solvent, with leaves showing the highest phenolic content (592.1 mg/100 g). Water remains the best solvent for flavonoid extraction, with flowers and leaves having the highest flavonoid concentrations (722.1 mg/100 g and 552.2 mg/100 g, respectively). Seed is the most nutritious, containing the highest amount of crude protein and nitrogen-free extract. Stem bark is rich in calcium (883 mg/kg) and potassium (3093 mg/kg). Amino acid analysis shows seeds are high in glutamic acid and aspartic acid, while proline is predominant in stem bark. Leaf tissue exhibits the strongest antibacterial activity against E. coli and S. aureus, suggesting its potential use in antibacterial applications. This demonstrates the research’s contributions to possible uses of Kenaf in health and nutrition.